Lowland Integrated Crop–Livestock Systems with Grass Crops Increases Pore Connectivity and Permeability, Without Requiring Soil Tillage - Jordano Vaz Ambus; Amanda Romeiro Alves; Douglas Leandro Scheid; Antonio Celso Dantas Antonino; José Miguel Reichert (Soil Systems)
Enhancing integrated crop–livestock systems (ICLSs) to improve land-use efficiency is a critical goal. Understanding the ICLS impacts on lowland soils is key to sustainable agricultural practices. Our objective was to test whether adopting ICLSs in lowlands improves soil structure, pore connectivity, and water and air permeability. This study was conducted in a long-term field trial, consisting of the following production systems with flood-irrigation rice: rice–fallow–rice, under conventional tillage and absence of grazing (RFR-ct); rice-grazed ryegrass–rice, under no-tillage and grazing (RGrR-nt); rice-grazed ryegrass–soybean-grazed ryegrass–rice, under no-tillage and grazing (RGrS/RGrR-nt); and a grazed pasture-consortium (winter) and succession field (summer), with no-till rice every 4 years (P4R-nt). Core samples were collected after grazing (October 2018), harvesting (March 2019), and grazing (October 2019). We analyzed soil air permeability, saturated hydraulic conductivity, pore connectivity by computed tomography. Soil tillage in a semi-direct system generated discontinuous porosity. Systems with intense trampling or less surface protection are affected by shearing on topsoil, reducing pore continuity. ICLSs are mainly composed of ryegrass–rice mitigated the harmful effects of trampling, and improved soil structure and functioning. Systems without soil tillage exhibited higher pore connectivity and pores with vertical orientation. Finally, soil tillage is not required to improve structural quality in ICLSs.